BREAST CANCER PREVENTION INTERVENTION THROUGH COMMUNITY EMPOWERMENT: A SOCIAL PERSPECTIVE IN BONTANG CITY - Asbi, Erni Asneli; Harahap, R. Hamdani; Zulfendri, Zulfendri; Daulay, Harmona (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Lambung Mangkurat, 2024)
Breast cancer is the most common type of cancer among women in Indonesia, with high mortality rates often attributed to late detection. This study aims to analyze breast cancer prevention interventions through community empowerment in Bontang City, focusing on the community’s social construction regarding knowledge, attitudes, and behaviors toward early breast cancer prevention. Using a qualitative, descriptive-exploratory approach, data were collected through in-depth interviews, focus group discussions (FGDs), observations, and documentation involving various stakeholders, including healthcare workers, local leaders, and the general public. Thematic analysis identified vital themes such as public knowledge gaps, limited awareness of early detection methods like self-examination (SADARI), and socio-cultural barriers. Results reveal that community empowerment plays a significant role in increasing awareness and participation in prevention programs. However, misinformation, limited access to healthcare services, and a lack of sustained support hinder optimal outcomes. Local policies that consider specific regional health needs, alongside collaborative efforts between the government, healthcare providers, and community organizations, are crucial to enhancing the effectiveness of breast cancer prevention interventions. This study offers theoretical contributions to developing community empowerment models in health prevention and provides practical recommendations for improving local health policies in Bontang.